Evaluation of placental chorionic villi histone 2A expression in HIV-infected women with pre-eclampsia. (February 2020) - Moodley, Merantha; Moodley, Jagidesa; Naicker, Thajasvarie
Abstract: Objective: Chorionic syncytiotrophoblasts (STB) function as an essential regulator of feto-maternal exchange. Therefore, STB actively differentiate to maintain their continuity for barrier function. However, the placental pathology reported in disorders such as pre-eclampsia (PE) threaten the homeostatic differentiation of STB. Since, HIV-1 requires the expression of co-receptors on STB to undergo vertical transmission, the aim of this study was to determine the effect of PE and HIV infection on the different stages of STB maturation [mature (H2A+) versus differentiating (H2A-)] and to immuno-localize and quantify the expression of histone 2A (H2A) i.e., positive (H2A+) and H2A negative (H2A-) nuclei within placental conducting and exchange villi. We also compared the expression of H2A + and H2A- nuclei between normotensive versus PE groups, HIV status and across the study population. Study design: Placental tissue was obtained from pregnant normotensive (n = 30) and pre-eclamptic (n = 30) women after informed written consent. The study groups were further categorized by their HIV status. Immunohistochemistry using the anti-histone 2A (H2A) antibody to identify fully differentiated functional (mature) STB was performed using conventional techniques. Morphometric image analysis was utilized to quantify placental histone H2A immuno-expression in placental exchange and conducting villi. Statistical analysis was performed using GraphPad Prism software. Results: H2A + and H2A- nuclei were immuno-localized within STB of the exchange and conducting villi with H2A- nuclei prominent on the periphery. In the exchange villi, the immuno-expression of H2A + and H2A- nuclei were lower in the PE group compared to the normotensive group ( p = 0.0003 and p < 0.0001 respectively). A reduced immuno-expression of H2A+ and H2A- nuclei was lower in exchange villi of HIV+ compared to HIV- placentae ( p = 0.0002 and p = 0.0276 respectively). Conclusions: PE and HIV reduces the percentage of H2A + and H2A- immuno-expression indicative of mature STB and actively differentiating STB respectively. We speculate that the different maturation states of STB and their orientation resultant of PE pathogenesis may be protective against the process of HIV-1 vertical transmission.